Uneven ground? Intersectional gender inequalities in the commercialized cassava seed system in Tanzania - Liani, M.L.; Cole, Steven M.; Mwakanyamale, Devis F.; Baumung, L.; Saleh, N.; Webber, A.; Tufan, Hale Ann; Kapinga, R. (Frontiers Media, 2023)
Cassava (Manihot esculenta Crantz) is an important crop in Africa, especially to women who rely on it as a household staple food and source of income. In Tanzania, a recent move toward commercializing the cassava seed system resulted in significantly fewer women than men farmers, known as Cassava Seed Entrepreneurs (CSEs), producing improved seed for sale to fellow farmers. To document the barriers and constraints that create gender inequalities in the seed system to better understand women’s low representation and experiences in commercialized cassava seed production, we carried out a mixed-methods study in the Southern, Eastern, and Lake Zones of Tanzania in 2021. The quantitative analysis found differences in key individual and household characteristics between CSEs and farmers who aspired to be but did not participate as CSEs (or A-CSEs) as well as between women CSEs and women A-CSEs. After running a logistic regression, results indicated that sex of the farmer (being male) was a statistically significant predictor of participating as a CSE (p < 0.05), along with having a secondary education (p < 0.05) and owning a bank account (p < 0.01). The qualitative analysis highlighted challenges women CSEs face. They spoke about having lower access to and control over prerequisite resources, which are shaped by other intersecting social identities such as marital status and age. Gender stereotypes about their capacities to manage their seed businesses can demotivate them from carrying out their work as well as experiences dealing with discriminatory gender norms that limit their travel to attend trainings outside their communities. Despite these barriers, some women CSEs expressed positive outcomes that have accrued from their participation in commercialized seed production, including enhanced social status and improved living standards. For the commercialized cassava seed system to be more socially inclusive and sustainable, we argue that there is need to adopt gender-aware approaches to address the underlying barriers and biases that exclude women and other social groups. Development efforts should consider combining social change innovations with seed system interventions to address the inequitable norms and power relations that create unique constraints for women to operate effectively as seed entrepreneurs.